The effects of nano-additives on exhaust emissions and toxicity on mankind - Norhafana, M.; M. M., Noor; A. A., Hairuddin; S., Harikrishnan; K., Kadirgama; D., Ramasamy (Elsevier Ltd, 2020)
Nanoparticle additives and water emulsified fuels have been reported by many researchers to be the best methods in emission control and improving engine performance. The effects of nano additives the engine combustion and exhaust emission are thoroughly discussed from numerous researches from the past. The temperature of the carbon combustion is lowered by Cerium Oxide which improves the oxidation of HC. Complete fuel combustion is then achieved this way. The nano additives are then further discussed of its effects to humans by way of toxicity, engine corrosion, real time applications and limitations that ensue. The liver and kidney are seen to be affected by nano materials due to its toxicity. In dosing nanoparticles additives in diesel and biodiesel that are dosed with nanoparticle additives are reported by most researchers to enhance the performance of engines and reduce emission characteristics. Ce2O3, Copper, water-based coolants and Al2O3 are the targeted nanomaterials. Thus, there are advantages and disadvantages of application nano-additives on engines and effects on humans.